Functional state of cardial and pyloric sphincters, sphincter of Oddi in children with non-differentiated connective tissue dysplasia and at absence of dysplasia - O. V. Drobysheva; O. K. Botvin’yev (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. Evaluation of the functional state of cardial and pyloric sphincters, as well as the sphincter of Oddi in children with non-differentiated connective tissue dysplasia and with no dysplasia.Material and methods. Eighty eight children with chronic gastroduodenitis were investigated: 50 – with non-differentiated connective tissue dysplasia (29 males and 21 females, aged 6–16 years) and 38 – without dysplasia (18 males and 20 females of the same age). All children underwent standard gastroenterological investigation. In patients of both groups functional state of cardiac and pyloric sphincters, along with the sphincter of Oddi was determined at gastroduodenoscopy. Besides that, the state of esophageal mucosa and frequency of reactive pancreatites (diagnosed according to changes of the pancreas at abdominal ultrasound and elevation of urine diastase level) were assessed.Results. Dysfunction of sphincters was revealed in 82% of children with dysplasia and in 84,2% – with no dysplasia. In children with connective tissue dysplasia no increase in frequency of motor disorders of cardiac and pyloric sphincters in comparison to children without dysplasia was revealed. At patients of both groups function of pyloric sphincter was usually normal. Dysfunction of cardiac sphincter was revealed at 52% of children with dysplasia and at 65,8% – without dysplasia, mostly – as incompetence and frequently was complicated by development of refluxes-esophagitis. Dysfunction of sphincter of Oddi in both groups occurred in 64 and 60,5% of cases respectively and mostly of the spastic type, promoting pancreatic lesion.Conclusions. Obtained data indicate necessity of complex investigation of children with diseases of gastro-intestinal tract and differentiated approach to treatment.